PERKAWINAN SIRRI DITINJAU DARI HUKUM ISLAM DAN HUKUM POSITIF - Bambang Ali Kusumo (Universitas Slamet Riyadi, 2011)
Abstract: Islamic law sees Sirri Marriage as something allowed to conduct; yet, it is highly recommended to record or to list it in an official marriage document. However, positive law sees it into two different point of views. Firstly, some experts consider sirri marriage as something legal to conduct. Secondly, some experts (and also law upholde opporatus) consider it as something prohibited. Following this idea, the goverment present a draf of marriage act to provide some punishments for people who conduct sirri marriage. Keywords: marriage, sirri marriage.